Near Infrared Fluorescent Nanostructure Design for Organic/Inorganic Hybrid System - Kyohei Okubo (MDPI AG, 2021)
Near infrared (NIR) light offers high transparency in biological tissue. Recent advances in NIR fluorophores including organic dyes and lanthanide-doped inorganic nanoparticles have realized the effective use of the NIR optical window for in vivo bioimaging and photodynamic therapy. The narrow energy level intervals used for electronic transition that involves NIR light, however, give rise to a need for guidelines for reducing heat emission in luminescence systems, especially in the development of organic/inorganic hybrid structures. This review presents an approach for employing the polarity and vibrational energy of ions and molecules that surround the luminescence centers for the development of such hybrid nanostructures. Multiphonon relaxation theory, formulated for dealing with heat release in ionic solids, is applied to describe the vibrational energy in organic or molecular systems, referred to as phonon in this review, and we conclude that surrounding the luminescence centers either with ions with low vibrational energy or molecules with small chemical polarity is the key to bright luminescence. NIR photoexcited phosphors and nanostructures in organic/inorganic mixed systems, designed based on the guidelines, for photodynamic therapy are reviewed.